Effects of decision synchronization on trust in collaborative networks - Daudi, Morice; Hauge, Jannicke; Thoben, Klaus-Dieter (Springer International Publishing, 2024)
Paper published by Springer International Publishing in the Conference of Collaboration in a Hyperconnected World: 17th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2016, Porto, Portugal, October 3-5, 2016, Proceedings 17 pp. 215–227, 2016.